Exploring the relationship between depression and delinquency: a sibling comparison design using the NLSY - Sims, Emma E.; Trattner, Jonathan D.; Garrison, S. Mason (Frontiers in Psychology, 2024)
Relative to the general population, adolescents with psychiatric disorders such as major depression disorder are incarcerated (and reincarcerated) at higher rates. Current research is mixed on whether this association is a cause, consequence, or the product of selection. For example, aggression can lead to more depressive symptoms, yet depression is associated with antisocial behaviors (e.g., delinquency). To better understand the relationship between depression and delinquent behavior, we used the discordant kinship model to examine data from sibling pairs in the National Longitudinal Surveys of Youth 1979, a nationally representative study. By explicitly modeling within- and between-family variance, we reduced the influence of genetic and shared-environmental confounds on our analysis. Our results suggest that the relationship between depression and delinquency is not causal, but rather a product of selection.